Legal Protection of Workers Under Civil Code and Job Creation Law - Edy Lisdiyono; Dina Imam Supaat (APPTHI, 2026)
Employment relations often place workers in a weaker bargaining position, increasing the risk of violations of their rights by employers. The enactment of the Job Creation Law (UU Cipta Kerja) has introduced greater labor flexibility while raising concerns about worker protection. This study analyzes the relevance of unlawful acts under Article 1365 of the Indonesian Civil Code in employment relations following the enactment of the Job Creation Law, identifies forms of unlawful acts committed by employers, and examines legal remedies available to workers. This research employs a normative legal method using statutory and conceptual approaches, supported by legislation, legal doctrines, and scholarly literature. The findings indicate that Article 1365 of the Civil Code remains an important complementary mechanism when labor law remedies are inadequate. Employers may be held liable for violations of normative rights, misuse of fixed-term employment agreements and outsourcing, unlawful termination, workplace harassment, occupational safety breaches, and privacy violations. Workers may seek material and immaterial compensation through civil litigation. The study emphasizes stronger harmonization between labor and civil law to ensure more effective and comprehensive protection of workers’ rights.